Comparison of 68Ga-FAP-2286 and 18F-FDG PET/CT in the diagnosis of advanced lung cancer - Xiang, Feifan; Zhang, Yue; Tan, Xiaoqi; Zhang, Jintao; Li, Tengfei; Yan, Yuanzhuo; Ma, Wenzhe; Chen, Yue (Frontiers in Oncology, 2024)
Purpose The 68Ga/177Lu-FAP-2286 is a newly developed tumor imaging agent that shows potential for visualizing and treating tumor stroma. The objective of this research was to evaluate the effectiveness of 68Ga-FAP-2286 PET/CT and 18F-FDG PET/CT in diagnosing advanced lung cancer. Methods In this prospective study, patients with lung cancer who underwent 68Ga-FAP-2286 and 18F-FDG PET/CT examinations between September 2022 and June 2023 were analyzed. Lesion uptake was converted to SUVmax. A paired T-test was used to compare the SUVmax, and the number of positive lesions detected by the two methods was recorded. Results In total, 31 participants (median age: 56 years) were assessed. The uptake of 68Ga-FAP-2286 was significantly higher than that of 18F-FDG in primary lesions (9.90 ± 5.61 vs. 6.09 ± 2.84, respectively, P < 0.001), lymph nodes (7.95 ± 2.75 vs. 5.55 ± 1.59, respectively, P=0.01), and bone metastases (7.74 ± 3.72 vs. 5.66 ± 3.55, respectively, P=0.04). Furthermore, the detection sensitivity of lymph nodes using 68Ga-FAP-2286 PET/CT was superior to that with 18F-FDG PET/CT [100% (137/137) vs. 78.8% (108/137), respectively], as well as for bone metastases [100% (384/384) vs. 68.5% (263/384), respectively]. However, the detection sensitivity for primary tumors using both modalities was comparable [100% (13/13) for both]. Conclusion Compared to 18F-FDG PET/CT, 68Ga-FAP-2286 PET/CT demonstrated better lesion detection capabilities for lung cancer, particularly in lymph nodes and bone metastases, providing compelling imaging evidence for the efficacy of 177Lu-FAP-2286 treatment.